2015
DOI: 10.1002/anie.201502569
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoephedrine‐Directed Asymmetric α‐Arylation of α‐Amino Acid Derivatives

Abstract: Available α-amino acids undergo arylation at their α position in an enantioselective manner on treatment with base of N'-aryl urea derivatives ligated to pseudoephedrine as a chiral auxiliary. In situ silylation and enolization induces diastereoselective migration of the N'-aryl group to the α position of the amino acid, followed by ring closure to a hydantoin with concomitant explulsion of the recyclable auxiliary. The hydrolysis of the hydantoin products provides derivatives of quaternary amino acids. The ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 82 publications
0
36
0
Order By: Relevance
“…[14] Thec lassical Smiles rearrangement proceeds by intramolecular S N Ar: [13,15] an activated, electron-deficient aryl ring migrates from OorSto N, with the heteroatoms in a1,4- [11a-c,15d] or 1,5-relationship. [11d, 14, 15a, 16] However, recent explorations of Nt oCaryl migrations in ureas, [17] have suggested that conformational preorganization [18] may promote intramolecular S N Ar reactions of even unactivated or electron-rich rings. N-Methylated benzanilides related to 5 prefer conformations in which the aryl rings lie cis, [19] and anthranilamide 5a was made to test the possibility that intramolecular N-arylation might proceed in such ac ompound by Smiles rearrangement, even of an unactivated ring.…”
mentioning
confidence: 99%
“…[14] Thec lassical Smiles rearrangement proceeds by intramolecular S N Ar: [13,15] an activated, electron-deficient aryl ring migrates from OorSto N, with the heteroatoms in a1,4- [11a-c,15d] or 1,5-relationship. [11d, 14, 15a, 16] However, recent explorations of Nt oCaryl migrations in ureas, [17] have suggested that conformational preorganization [18] may promote intramolecular S N Ar reactions of even unactivated or electron-rich rings. N-Methylated benzanilides related to 5 prefer conformations in which the aryl rings lie cis, [19] and anthranilamide 5a was made to test the possibility that intramolecular N-arylation might proceed in such ac ompound by Smiles rearrangement, even of an unactivated ring.…”
mentioning
confidence: 99%
“…Thus, not only methyl but also benzyl( Ta ble 4, entries 12 and 13) and other alkyl (Table 4, entry 14) and functionalizedc hains (Table4,e ntries 15 and 16) were tolerated at the substrate C 5 position without affecting the reaction efficiency or selectivity.O nthe otherh and, N 3 -aryl substrates 20-24 bearinga ryl groups other than phenyl also Scheme4.Catalyst screening for the reaction of 19 A with nitrostyrene. participated in this reactions atisfactorily (Table 4, entries [17][18][19][20][21]. Vinyl ketones were also competent electrophilic partnersi n the reactions of N 3 -substituted 2-benzylthioimidazolones 19-24.H owever,i nc ontrast to that observed with nitroalkenes, the reactions involving vinyl ketones followed two divergent pathways:o ne producing 5-additionp roducts 40 ando ne producing 3-additionp roducts 40' (Scheme 5).…”
Section: Preparation Of Substratesmentioning
confidence: 97%
“…[19] Only very recentlyh ave practical syntheses of enantiomerically enriched quaternary hydantoins involving new carboncarbon bond-formingr eactions been reported. Clayden developed an elegant protocol to access quaternary hydantoins and compounds derived thereofw ith good diastereoselectivity on the basis of as ubstrate-controlleda nionic aryl group N!Cr earrangement on lithiated ureas [20] (Figure2a). On the other hand, Te rada recently reported ac hiral phosphoric acid catalyzed Friedel-Crafts-type addition of 2-methoxyfuran to in situ generated ketimines (Figure 2b).…”
Section: Introductionmentioning
confidence: 99%
“…The use of ap seudoephedrine chiral auxiliary was also shown to enable enantioselective a-arylation of amino acid derivatives by Clayden and co-workers( Scheme 39). [57] The rearrangemento f131 leads to the formation of hydantoin 132 through cyclization and expulsion of the pseudoephedrine auxiliary,which could be readily recovered. Initial investigations of strongb ases gave very poor enantiomeric ratios in the hydantoinp roduct.…”
Section: Scheme34 Lithiation/aryl Migration Of Ureas and (Thio)carbamentioning
confidence: 99%